PUBLIC INFORMATION SYMBOLS IN TOURISM: IMPORTANCE, CHALLENGES, DIMENSIONS AND EMPIRICAL RESEARCH - Fiori, Sérgio Ricardo (Revista Brasileira de Cartografia, 2014)
After the 1970's, tourism becomes an economic and social practice of great importance worldwide. Two major factors are decisive in this change: first, the space becomes smaller due to technological progress, which reduces physical distances by means of transport (displacement) of passengers and communication (satellite). At the same time, socioeconomic changes as the gradual reduction of working hours (forty weekly hours, weekends and paid holidays), increasing the purchasing power of a significant portion of the population (growing of the middle class in many countries) and the raising of the educational level open the way for the change. In this historical context, the pictograms, also called Public Information Symbols, are becoming increasingly important, as are established as facilitators in the media. The graphic feature is used in daily life, being enhanced in environments that shelter many different cultures and nationalities, which have limitations to understand and express themselves in other languages, either at airports, exhibition venues, fairs and international events, historic centers, etc. The paper aims at the importance of these symbols for contemporary society, highlighting some challenges related to the development and / or use of pictograms (language, time and culture) and the lack of global standardization. Subsequently, it presents a substantiation of sign projection dimensions followed by an empirical research with eighty-two Public Information Symbols.